BALANCING INVESTOR PROTECTION AND SOVEREIGNTY: THE EVOLUTION OF BILATERAL INVESTMENT TREATIES AND INVESTOR-STATE DISPUTE SETTLEMENT IN INTERNATIONAL INVESTMENT LAW - Farid Nasirli (Western European Studies, 2025)
International investment law has evolved into a complex and dynamic field centered around a network of agreements and legal mechanisms aimed at safeguarding foreign direct investment (FDI). At the heart of this regime lie Bilateral Investment Treaties (BITs) and the InvestorState Dispute Settlement (ISDS) system. BITs are international agreements typically concluded between two States to promote and protect investments made by investors from one State in the territory of the other. Meanwhile, ISDS provides a procedural framework that allows foreign investors to bring claims directly against host States for alleged breaches of treaty obligations.
Keywords: Bilateral Investment Treaties; Investor–State Dispute Settlement; Foreign Direct Investment